Do universal adhesives promote bonding to dentin? A systematic review and meta-analysis - Ali A. Elkaffas; Hamdi H. H. Hamama; Salah H. Mahmoud (Restorative Dentistry & Endodontics)
ObjectivesThe aims of this study were to conduct a systematic review of the microtensile bond strength (µTBS) of multi-mode adhesives to dentin and to perform a meta-analysis to assess the significance of differences in the µTBS of one of the most commonly used universal adhesives (Scotchbond Universal, 3M ESPE) depending on whether the etch-and-rinse or self-etch mode was used.Materials and MethodsAn electronic search was performed of MEDLINE/PubMed, ScienceDirect, and EBSCOhost. Laboratory studies that evaluated the µTBS of multi-mode adhesives to dentin using either the etch-and-rinse or self-etch mode were selected. A meta-analysis was conducted of the reviewed studies to quantify the differences in the µTBS of Scotchbond Universal adhesive.ResultsOnly 10 studies fulfilled the inclusion criteria for the systematic review. Extensive variation was found in the restorative materials, testing methodologies, and failure mode in the reviewed articles. Furthermore, variation was also observed in the dimensions of the microtensile testing beams. The meta-analysis showed no statistically significant difference between the etch-and-rinse and self-etch modes for Scotchbond Universal adhesive (p > 0.05).ConclusionsMulti-mode ‘universal’ adhesives can achieve substantial bonding to dentin, regardless of the used modes (either etch-and-rinse or self-etch).